OVERVIEW OF THE IMPLEMENTATION OF CHSE CERTIFICATION IN HOTEL SERVICES IN THE YOGYAKARTA SPECIAL REGION OF INDONESIA - Sapto Hariyono; Sujoko (International Journal of Innovative Technologies in Social Science, 2023)
The impact of Covid-19 has brought more attention to tourism. The scale of the threat and risk posed by the Covid-19 pandemic is significantly reducing the willingness of tourists to stay in hotels. Cleanliness, Health, Safety and Environmental Sustainability (CHSE) promotes a clean, healthy, safe and friendly environment. CHSE is a policy implemented by the government, specifically the Indonesian Ministry of Tourism and Creative Industries, to prevent the spread of the Covid-19 pandemic in Indonesia. The purpose of this study is to review the impact of the pandemic on the hotel service sector and the extent of the implementation of CHSE in the hotel service sector in the special region of Yogyakarta. This study was conducted to see the extent to which CHSE certification is applied to the hotel sector in the Yogyakarta area. Data collection was carried out with secondary data presented on the official government website regarding CHSE-certified hotels, data for all hotels both in terms of room availability, number of rooms in the era before the pandemic and after the epidemic. Then analyzed with descriptive statistics and SPSS analysis with paired t-test for further discussion and conclusions drawn. Based on this research data, it is known that COVID-19 has a significant impact on tourist visits and the number of hotel rooms sold. The number of tourists both local and tourists foreign experienced a significant decline at the peak of the pandemic in 2020 in a row (p=0,016) and (p=0,032), but began to rise again in 2021. Likewise, the number of hotel rooms sold experienced a significant decline at the peak of the pandemic in 2020 (p=0,000) but began to rise again in 2021. data on This study also shows that the number of hotels that have been certified CHSE is still very low in the special area of Yogyakarta, which is 18.79%, so it is recommended that more hotels apply for CHSE certification to increase tourist interest in staying, visitor satisfaction, and a sense of trust and comfort visitors.